Mechanisms of Gap Junction Traffic in Health and Disease - Hesketh, Geoffrey G. (2009)
Gap junctions (GJs) allow direct communication between cells. In the heart, GJs mediate the electrical coupling of cardiomyocytes and as such dictate the speed and direction of cardiac conduction. A prominent feature of acquired structural heart disease is remodeling of GJ protein expression and localization concomitant with increased susceptibility to lethal arrhythmias, leading many to hypothesize that the two are causally linked. Detailed understanding of the cellular mechanisms that regulate GJ localization and function within cardiomyocytes may therefore uncover potential therapeutic strategies for a significant clinical problem. This review will outline our current understanding of GJ cell biology with the intent of highlighting cellular mechanisms responsible for GJ remodeling associated with cardiac disease.